Temperature Effects on Intensity Distribution at Emage Plane - Mohammed, A. A; A.Twiage, D.A; Aldene, D. J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To evaluate the effects of the thermal analysis and temperature of the atmospheric heat on the optical system. it varying the thermal expansion  (positive  or  Negative  Values)  of  the  material  and  then changes the characteri of the optical system properties such as radius of curvetur of the surfaces, size of the aperture stop     ect.This paper  had calculated the accepted ratio of the temperature variable   on the optical system during analyzing the effect of thermal analysis on the Radial Energy Distribution for +20C0 and +50C0  â€¢